PENGARUH PEMBERIAN COKELAT HITAM (DARK CHOCOLATE) TERHADAP PENURUNAN SKALA NYERI HAID (DISMENHOREA PRIMER)PADA REMAJA PUTRI KELAS 8 DI SMP NEGERI 1 DELI TUA KECAMATAN DELI TUA KABUPATEN DELI SERDANG - Yanti, Mutiara Dwi; Sitepu, Stefani Anastasya; pebriani, winda maya (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
early life is a completely important period of development for kids, which is marked through the maturity of the physical (sexual) organs so that later they may be able to reproduce. Menstrual ache (dysmenorrhea) is pain or cramping inside the decrease abdomen, which appears before or at some point of menstruation. Menstrual ache is normally felt by means of women on the first day of menstruation. remedy of dysmenorrhea can be achieved with pharmacological and non-pharmacological remedy. To find out the impact of giving dark chocolate (darkish chocolate) on lowering menstrual ache scale (number one dysmenorrhea) in grade 8 teenage girls at SMP Negeri 1 Deli Tua, Deli Tua sub-district, Deli Serdang Regency in 2023. The sort of studies used was the only organization Pre take a look at and post take a look at layout, particularly a study conducted to evaluate one group. Respondents, specifically the complete populace, might be used as a pattern, particularly all fifteenth grade younger women. The results of bivariate evaluation using the Stastic wilcoxon acquired p = 0.000 (p <0.05) so it was validated that there has been an effect of giving darkish chocolate to a decrease in menstrual ache scale (number one dysmenorrhea) in grade 8 adolescent women at SMP N 1 Deli old yr 2023.